The Benefits and Harms of Cleansing for Acute Traumatic Wounds: A Narrative Review. (September 2021) - Wynn, Matthew
ABSTRACT: Acute traumatic wound cleansing is currently a controversial issue demonstrated by the variability in solutions and techniques used to clean wounds in clinical practice. Although there is evidence of improved infection outcomes in wounds cleansed with antiseptics, these observations are often undermined by concurrent use of antibiotics in addition to poor study design. Cleansing techniques including pressurized irrigation have also been investigated indicating potential harms such as edema and inconsistencies in irrigation pressures. The purpose of this article is to provide a narrative review on the contemporary evidence indicating the potential harms and benefits of wound cleansing in the context of acute traumatic wounds. This literature review reveals that acute wound cleansing in clinical practice remains heavily dependent on tradition rather than robust clinical evidence. The evidence base remains limited because of methodological and pragmatic issues in obtaining definitive data on the efficacy of specific agents and techniques. Future studies should focus on establishing the relative benefits of different cleansing solutions and techniques. Establishing the most effective use of antiseptic cleansing solutions may also help reduce further antimicrobial resistance as observed in recent studies. Clinicians responsible for cleansing wounds must consider patient preference when deciding which solution and techniques are used. In addition, a risk assessment considering the potential harms and benefits of different solutions and techniques must be performed.